Identification of Protease-Producing Halophilic Bacteria Isolated from Salt-Pond Soil - Asep Awaludin Prihanto; Rahmi Nurdiani; Hidayatun Muyasharoh; Jauharotul Afifah (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsThe halophilic bacteria were isolated from salt-pond soil.Isolate C2 was identified as the best protease producer.Isolate C2 was identified as B. amyloliquefaciens strain UBCAbstractProtease is an important enzyme for various industries, such as pharmaceuticals, leather production, meat processing, protein hydrolyzate, food products, and waste processing industries. This study aimed to isolate and identify protease-producing bacteria isolated from salt-pond soil at the Tuban Regency, East Java, Indonesia. Bacterial communities in the soil samples were firstly isolated from the soil samples by culture-dependent technique on Luria Bertani agar enriched with 5% NaCl. Thereafter, bacterial colonies that grew on the media were purified and screened for their protease production using a skim-milk agar. The bacterial colony which produced protease was further identified using phenotypic (gram staining) and genotypic assays (the 16S rDNA sequence). The result showed that one isolate out of six (isolate C2) obtained from the soil sample was observed to produce a protease enzyme. Based on its 16S rDNA sequence, the isolate was identified as Bacillus amyloliquefaciens strain UBC. These results suggest that B. Amyloliquefaciens strain UBC is a salt-tolerant bacterium (halophilic bacteria) which has the potential to be further developed for protease-producing biological agents.